1996
DOI: 10.1017/s0952675700002682
|View full text |Cite
|
Sign up to set email alerts
|

Place assimilation is not the result of gestural overlap: evidence from Korean and English

Abstract: In the theory of articulatory phonology Browman & Goldstein (1986, 1990, 1992) claim that place assimilation is mainly the result of the overlap of gestures and the perception of these overlapping gestures as a single gesture. Ohala (1990) makes a similar claim. The present study provides interesting experimental evidence against this explanation of assimilation as a result of gestural overlap and resulting misperception, and for the importance of gestural reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 11 publications
1
33
1
Order By: Relevance
“…Articulatory and acoustic evidence suggests that assimilation may pose an even more complicatedfeature-parsing problem, given the information encoded in the physical realizationof assimilated segments. Although there is some debate over whether natural assimilation ever creates complete or categorical change in acoustic feature cues (Gow, 2003;Nolan, Holst, & Kuhnert, 1999), all existing articulatory and acoustic evidence shows that this process often leads to gradient modification of place of articulation (Barry, 1985;Gow, 2001Gow, , 2002Gow, , 2003Holst & Nolan, 1995;Jun, 1996;Kerswill, 1985;Nolan et al, 1996). Articulatory descriptions of place assimilation focus on two factors.…”
Section: English Place Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Articulatory and acoustic evidence suggests that assimilation may pose an even more complicatedfeature-parsing problem, given the information encoded in the physical realizationof assimilated segments. Although there is some debate over whether natural assimilation ever creates complete or categorical change in acoustic feature cues (Gow, 2003;Nolan, Holst, & Kuhnert, 1999), all existing articulatory and acoustic evidence shows that this process often leads to gradient modification of place of articulation (Barry, 1985;Gow, 2001Gow, , 2002Gow, , 2003Holst & Nolan, 1995;Jun, 1996;Kerswill, 1985;Nolan et al, 1996). Articulatory descriptions of place assimilation focus on two factors.…”
Section: English Place Assimilationmentioning
confidence: 99%
“…Thus, the two gestures appear to be fused into one acoustic landmark, consistent with the production of just one segment. Jun (1996) has argued that overlap alone is insufficient to create perceived assimilation. Jun found that assimilation also requires reduction of the assimilated segment.…”
Section: English Place Assimilationmentioning
confidence: 99%
“…Instances of perceived assimilation can be described similarly with reference to gestures being 'hidden' as a result of temporal reduction. There is also experimental evidence that in these environments the relevant articulatory gestures are subject to reduction in magnitude (Jun, 1996;Jaeger and Hoole, 2007), which may make them more susceptible to being 'hidden' by another gesture. Instances of lenition of the whole juncture (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…If there is a labial in C1, only a velar in C2 can be a trigger. Recently, articulatory studies on place assimilating languages have also improved our understanding in research on variability in the articulation of consonants from various languages such as American English, British English, German, Georgian, Korean, Russian, Spanish, Swedish (Browman & Goldstein, 1990Chitoran, Goldstein, & Byrd, 1992;Jun, 1995Jun, , 1996Jun, , 2004Honorof, 1999;Kühnert, Hoole, & Mooshammer, 2006;Kochetov & Pouplier, 2008;Son, Kochetov, & Pouplier, 2007;Kochetov, Pouplier, & Son, 2007;Son, 2008aSon, , 2008bSon, , 2011aSon, , 2011b. In particular, results from articulatory studies have shown that place assimilation occurred to some extent either as gestural overlap between the target and the trigger, spatiotemporal reduction of the target stop, or both (Jun, 1995(Jun, , 1996(Jun, , 2004Nolan, 1992;Kühnert & Hoole, 2004;Son et al, 2007;Kochetov & Pouplier, 2008;Son, 2008b among others).…”
Section: Autosegmental Phonology Within the Tradition Of Classicalmentioning
confidence: 99%